ANALISIS SEMIOTIKA RASISME DALAM FILM NIGHT SCHOOL - Dinul Huda; Tutut Ismi Wahidar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
As one of the media that reflects American society, Hollywood films still have many elements of racism that are poured into several film genres. One of the most popular genres is comedy, such as the one in the film Night School , which was released in 2018. This film shows a lot of acts of racism that are deliberately used as a supporting element of comedy to invite laughter from the audience. This research uses qualitative research methods and is analyzed with the theory of Roland Barthes. The subject in this study is the film Night School genre comedy which has a duration of 1 hour 34 minutes in total and consists of 56 scenes, then the researcher selects one by one scene that contains acts of racism. Based on the analysis results obtained in the film Night School , namely this film can be found symbols both verbal and non-verbal that can be analyzed with semiotics. There are denotative meanings, connotations and myths that lead to acts of racism in this film. Researchers found the denotative meaning of this film, which is a comedy about the struggle of a black man to get a high school diploma to get a job, besides that there is also a connotative meaning, namely a film that shows the racism that is still strong in America against a person's physical and race. The myth that researchers found in this film is about racism, namely black people are still considered stupid, black people are troubling because they tend to commit criminal acts, people who have short bodies are easier to intimidate, black people have a lower social status than white people, and the issue of Islamophobia in America is still strong. Keywords : Film, Racism